O discurso dos ursos e os processos de subjetivação da homoafetividade - Silva, José Josemir Domingos da (2009)
This dissertation, which is entitled The Discourse of the Bears and the T Subjectivity Processes of the Homoaffectivity intends to describe and to analyze modes of subjectivity became discourse in profiles of homoaffective people, who named themselves bears, registered in relationship sites targeted in this homosexual group. The work is based on theories of Discourse Analysis French, focusing on the thematic subject-discourse-enunciate, and in discussions of Michel Foucault about sexuality and processes subjectivity, understood through the production of meanings of discursive practices. For its qualitative / interpretive and write in scope of language studies, this research develops into a method attentive to historical and cultural realities of the subject by introducing points of convergence with other fields of knowledge whose interest is on the subject, discourse and sexuality. Data analysis indicates that the sites chosen for this study are spaces of sociality bears and enable the exchange of information and experiences among bears in different parts of the world. Moreover, they function as discursive spaces where the homosexual bear sustains and gives meaning to their subjectivity. Thus, the analysis of images and selected profiles, it is possible to produce some effects of meaning on the discursive construction of homosexual bear. The bear is presented cleaved by several other places of enunciating. Through discursive practices, the bear repeats the model of heteronormative masculinity through physical performance of the body. The repetition of a male body grammar becomes problematic idea of "naturalness" of gender identities and sexual. Once you understand the bear as a subjective construction underway, the becoming, as such, it falls in a social-historical specific moment where it was possible irruption in homoaffective practices.